Zanubrutinib is well tolerated and effective in patients with CLL/SLL intolerant of ibrutinib/acalabrutinib: updated results - Mazyar Shadman; John M. Burke; Jennifer Cultrera; Habte A. Yimer; Syed F. Zafar; Jamal Misleh; Subramanya S. Rao; Charles M. Farber; Aileen Cohen; Hui Yao; Adam Idoine; Qi An; et al. (Blood Advances)
Abstract: Bruton tyrosine kinase (BTK) inhibitors such as ibrutinib (ibr) revolutionized chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) treatment, although treatment-related toxicities limit the use of some BTK inhibitors. Zanubrutinib, a potent next-generation BTK inhibitor, has higher selectivity than ibrutinib or acalabrutinib. The ongoing phase 2, single-arm BGB-3111-215 study investigates the safety and efficacy of zanubrutinib in patients with B-cell malignancies who are intolerant of ibrutinib and/or acalabrutinib. Here, results in patients with CLL/SLL are presented. Patients received zanubrutinib 160 mg twice daily or 320 mg once a day. With a 34.5-month median follow-up, 71 patients (ibrutinib intolerant only, n = 44; acalabrutinib intolerant only, n = 17; ibrutinib and acalabrutinib intolerant, n = 10) received ≥1 zanubrutinib dose. On zanubrutinib, 54% (28/52) of ibrutinib-intolerant patients and 70% (19/27) of acalabrutinib-intolerant patients experienced no recurrence of intolerance adverse events (AEs); 60% and 72% of intolerance AEs did not recur, respectively. Of recurrent ibrutinib-intolerance AEs, 64% were lower grade; 44% of acalabrutinib-intolerance AEs were lower grade. No intolerance AEs recurred at a higher grade with zanubrutinib. The most common recurrent ibrutinib-intolerance and acalabrutinib-intolerance AEs were fatigue and diarrhea, respectively. The most common treatment-emergent AEs (TEAEs) with zanubrutinib were fatigue (32%) and COVID-19 (28%). Grade ≥3 TEAEs occurred in 61%, serious TEAEs in 32%, and TEAEs leading to discontinuation in 11%. Of 67 efficacy-evaluable patients, 94% experienced disease control: 30% had a best response of stable disease and 64% had a partial or complete response. These data demonstrate that patients intolerant of ibrutinib/acalabrutinib may benefit from switching to zanubrutinib therapy. This trial was registered at www.ClinicalTrials.gov as #NCT04116437.